2012
DOI: 10.4314/njp.v39i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal exposure to intimate partner violence on under-five mortality in Nigeria

Abstract: Background:The under-5 mortality rate in many developing countries has shown little or no improvement over the years. Ravaged by war and poverty, violence which is now a norm in most African countries (including Nigeria) is on the increase and has condensed into most families with women and children bearing the major brunt of this violence. Aim: Effect of maternal exposure to intimate partner violence on under-5 mortality in Nigeria. Methods: Data from nationally representative sample of mothers (aged 15-49 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…This finding is consistent with the lifetime prevalence of IPV in sub-Saharan Africa and Nigeria (Jewkes et al, 2002;Osuora et al, 2012). The high prevalence of IPV found in this study could suggest the patriarchal ideology in traditional societies such as Nigeria where gender roles are being skewed to justify violence against women who are assigned an inferior role to men (Antai, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with the lifetime prevalence of IPV in sub-Saharan Africa and Nigeria (Jewkes et al, 2002;Osuora et al, 2012). The high prevalence of IPV found in this study could suggest the patriarchal ideology in traditional societies such as Nigeria where gender roles are being skewed to justify violence against women who are assigned an inferior role to men (Antai, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Emenike and colleagues (2008) found a significant association between physical/emotional/sexual abuse of women and negative reproductive health outcomes such as terminated pregnancies and infant mortality. In Nigeria, women's exposure to IPV was associated with low use of contraception, miscarriages, induced abortion, and child mortality (Okenwa, Lawoko, & Jansson, 2011;Osuora et al, 2012). Antai (2011) found a strong association between IPV and traumatic physical consequences.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Regional differences in childhood mortality have been linked to variations in the socio-economic characteristics and utilisation of maternal and child health care services [212223]. Studies that focussed on the relationship between maternal employment and childhood mortality are rare, though a few included maternal employment as a control variable [242526].…”
Section: The Nigeria Contextmentioning
confidence: 99%
“…1 Some other researchers examined the interaction between intimate partner violence and childhood mortality. 24 In such studies, 25 it was observed that infant and neonatal mortality was greater among children whose mothers experienced intimate partner violence versus those whose mothers did not experience intimate partner violence. The primary explanation of the influence of violence against women on the risk of neonatal and infant mortality is the possible constraining effect of such violence upon women's ability to physically and emotionally care and provide for their children's basic needs.…”
Section: Introductionmentioning
confidence: 99%